Association of jasmonic acid priming with multiple defense mechanisms in wheat plants under high salt stress - Sheteiwy, Mohamed S.; Ulhassan, Zaid; Qi, Weicong; Lu, Haiying; AbdElgawad, Hamada; Minkina, Tatiana; Sushkova, Svetlana; Rajput, Vishnu D.; El-Keblawy, Ali; Jośko, Izabela; Sulieman, Saad; El-Esawi, Mohamed A.; et al. (Frontiers in Plant Science, 2022)
Salinity is a global conundrum that negatively affects various biometrics of agricultural crops. Jasmonic acid (JA) is a phytohormone that reinforces multilayered defense strategies against abiotic stress, including salinity. The present study investigated the effect of JA (60 µM) on two wheat cultivars, namely ZM9 and YM25, exposed to NaCl (14.50 dsm-1) during two consecutive growing seasons. Morphologically, plants primed with JA enhanced the vegetative growth and yield components. Seed priming with JA increased photosynthetic pigments, stomatal conductance, intercellular CO2, maximal photosystem II efficiency, and transpiration rate of the stressed plants. The swollen chloroplasts with disintegrated grana and plastoglobuli numbers were higher in JA-primed plants than non-stressed plants. Furthermore, JA prevented dehydration of leaves by increasing relative water content and water use efficiency (WUE) via reducing water and osmotic potential using proline as an osmoticum. There was a reduction in sodium (Na+) and increased potassium (K+) contents, indicating a significant role of JA priming in ionic homeostasis, which was associated with induction of the transporters, viz., SOS1, NHX2 and HVP1. JA induced the levels of endogenous cytokinins, indole acetic acid (IAA) and JA salt-stressed plants, but reduced the level of abscisic acid (ABA) relative to salinity stressed plants only. In addition, the oxidative stress caused by increasing hydrogen peroxide in salt-stressed plants was restrained by JA, which was associated with increased α-tocopherol, the phenolics and flavonoids levels and superoxide dismutase and ascorbate peroxidase activity. This increase in phenolics and flavonoids could be explained by the induction of phenylalanine ammonia-lyase activity. The results suggest that JA plays a key role at the morphological, biochemical, and genetic levels of stressed and non-stressed wheat plants. Hierarchical cluster analysis and Principal Component analyses showed that salt sensitivity was associated with the increments of Na+, hydrogen peroxide, and ABA contents. The regulatory role of JA under salinity stress was interlinked with increased JA level which consequentially improved ion transporting, osmoregulation and antioxidant defense